Digital mucous cyst - case report - Emilia Jakimcio-Turowska; Jacek Sompor; Małgorzata Przyszlak-Szabała; Jadwiga Sierocińska-Sawa; Małgorzata Michalska-Jakubus; Dorota Krasowska (Termedia Publishing House, 2014)
Introduction . Digital mucous cyst is a benign, translucent nodule that occurs on the dorsum of the finger. The cyst is filled with a gelatinous mass and connected with the interphalangeal joint. Arthritis plays the main role in the etiology. Objective . To present a case of digital mucous cyst and its therapeutic difficulties. Case report . A 60-year-old patient was admitted to the Outpatient Clinic of Dermatology because of a soft, periungual nodule on the left third finger. The clinical picture suggested a mucous cyst. Many treatment methods were used with varying therapeutic efficacy (puncture, electrocoagulation, cryotherapy, surgery). Conclusions . The choice of treatment is individual, but in our case, surgical removal of the lesion was most efficacious.